3-D crustal VS model of western France and the surrounding regions using Monte Carlo inversion of seismic noise cross-correlation dispersion diagrams. Issue 3 (18th November 2020) - Gaudot, I; Beucler, É; Mocquet, A; Drilleau, M; Haugmard, M; Bonnin, M; Aertgeerts, G; Leparoux, D
SUMMARY: Due to a too sparse permanent seismic coverage during the last decades, the crustal structure of western France and the surrounding regions is poorly known. In this study, we present a 3-D seismic tomographic model of this area obtained from the analysis of 2-yr continuous data recorded from 55 broad-band seismometers. An unconventional approach is used to convert Rayleigh wave dispersion diagrams obtained from ambient noise cross-correlations into posterior distributions of 1-D VS models integrated along each station pair. It allows to avoid the group velocity map construction step (which means dispersion curve extraction) while providing meaningful VS posterior uncertainties. VS models are described by a self-adapting and parsimonious parametrization using cubic Bézier splines. 1268 separately inverted 1-D VS profiles are combined together using a regionalization scheme, to build the 3-D VS model with a lateral resolution of 75 km over western France. The shallower part of the model (horizontal cross-section at 4 km depth) correlates well with the known main geological features. The crystalline Variscan basement is clearly associated with positive VS perturbations while negative heterogeneities match the Mesocenozoic sedimentary basins. At greater depths, the Bay of Biscay exhibits positive VS perturbations, which eastern and southern boundaries can be interpreted as the ocean−continent transition. The overall crustal structure below the Armorican Massif appears to be heterogenous at the subregional scale, and tends to support that both the South-Armorican Shear Zone and the Paris Basin Magnetic Anomaly are major crustal discontinuities that separate distinct domains.